ENSURING PATIENT RIGHTS AND SAFETY: LEGAL PROTECTION IN THE 2023 HEALTH LAW FOR SAFE AND QUALITY MEDICAL SERVICES - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Safe and quality healthcare is a human right that must be guaranteed by the state. Law No. 17 of 2023 on Health serves as a regulation that strengthens the guarantee of patients' rights and safety in the healthcare system in Indonesia. This study aims to analyse the legal protection of patients' rights and safety guarantees as regulated in the 2023 Health Law. Using a normative juridical research method through a legislative and conceptual approach, this study found that patients' rights are protected more comprehensively, including the right to medical information, consent to medical treatment, confidentiality of medical records, emergency services, safe medicines, and dispute resolution mechanisms. On the other hand, the concept of patient safety is strengthened through the obligation of health facility accreditation, the application of quality standards, incident reporting systems, drug and health technology supervision, and the obligation of health worker competence. The legal protection provided by the 2023 Health Law is both preventive and repressive, while placing patient safety as the main indicator of quality medical services. Thus, this law serves as a strategic legal foundation for building a national health system that is more equitable, safe, and oriented towards human dignity.